EXTENDED SPECTRUM Î²-LACTAMASES IN ENTERIC GRAM-NEGATIVE BACILLI: RELATED TO AGE AND GENDER - Mumtaz, Shamim; Ahmad, Mumtaz; Aftab, Irum; Akhtar, Naeem; Hassan, Masood ul; Hamid, Abdul (Journal of Ayub Medical College Abbottabad, 2007)
Background: Extended Spectrum Î²-Lactamases (ESBLs)-producing strains of Enterobacteriaceae have emerged as a major problem in hospitalized as well as community based patients. Infections due to ESBLs-producers range from uncomplicated urinary tract infection to life threatening sepsis .The objective of this study was to find out the prevalence of ESBLs-producing Gram- negative bacilli among clinical isolates. Methods: This descriptive study was conducted at the Microbiology department of Fauji Foundation Hospital, Rawalpindi over a period of two years (March 2004-April 2006). Six hundred and nine isolates of Enteric Gram-negative rods from various samples were tested for ESBLs- production by double disc synergy test. In 176 ESBLs-producing isolates, source of samples in term of indoor/outdoor was analyzed. In 165 ESBLs-producing isolates, patients' gender and age was analysed from 3 months to 70 years. Results: The ESBLs-producing isolates were more commonly isolated from indoor patients (88.1%) as compared to outdoor patients (11.9%). Escherichia coli was found to be most prevalent organism in indoor patients while Klebsiella pneumoniae, was the most prevalent organism in outdoor patients. ESBLs were most commonly isolated from female patients (64.3%) suffering from urinary tract infections ((41.5%), as compared to male patients (35.7%) in which the organisms were most commonly isolated from pus samples (54.2 %). ESBLs-producing Enteric Gram-Negative rods were most frequent at later part of life where they were most common (27.9%) at 61-70 years, followed by 41-50 years of age group (20.0%). Another peak (13.3%) was also seen at younger age group (11-20 years). The least prevalence (5.5%) was seen in two age groups (0-10 and 31-40 yrs). In case of female patients, ESBLs-producing EGNR were most frequently (29.2%) isolated from middle age group (41-50 years) followed by later age groups (51-60 and 61-70 years, (15.1% and 25.5%). Conclusions: Considering the high prevalence of ESBLs in Enteric Gram-negative rods, it is suggested that all such isolates should be tested for the production of ESBLs in the routine microbiology laboratory. Key Words: Extended-Spectrum Beta-lactamases, Enterobacteriaceae, Enteric Gram-Negative rods, Escherichia coli, Klebsiella pneumoniae, Enterobacter spp